A Setback to the Dialogue: Response to Huston Smith - Goodenough, Ursula (Zygon, 2001)
Huston Smith's book, Why Religion Matters, offers an eloquent evocation of mystical sensibility. Unfortunately, along the way, he offers a strongly negative and often inaccurate account of the scientific worldview, the claim being that the science is laying siege to the spiritual.